Power and profit : British colonial trade in America and the Caribbean, 1678-1825. - National Archives (Great Britain) (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
These lists cover a range of ports in and near to the East Coast of the American Continent, from Nova Scotia to Suriname. Commencing with Nova Scotia, they cover New Hampshire, Massachusetts, New Jersey, Maryland, Virginia, South Carolina, Bermuda, Georgia, Florida, the Bahamas, Jamaica, the British Virgin Islands, Saint Kitts and Nevis, Antigua, Montserrat, Dominica, Martinique, Saint Vincent, Barbados, Grenada, Trinidad and Tobago, Guyana, and Suriname. The naval office shipping lists were compiled by the naval officers in the British colonies in North America and the West lndies and then sent periodically, usually every three months, by the Governor of the colony to the Board of Trade or the Treasury in England. Like other governmental records, they were subsequently deposited in the Public Record Office, London, where they are now to be found. The shipping lists were working documents and many factors can account for their loss and destruction. Many lists, it may be surmised, were destroyed by a fire in the Plantation Wing of the London Custom House in 1814. Other lists were probably never despatched from the colonies or were lost in transit to England, whilst in London some of them, no doubt, were mislaid, mixed up with other papers or otherwise separated from the main collection. Consequently none of the series are complete. The information the naval office lists contain includes: the date of entry or clearance, the name of the ship and the home port or colony, the details of the vessel's construction and registration (where and when built and where and when registered), the name of the master, the name of the owner(s), the tonnage, the number of guns carried, the number of crew, and the cargo carried (including slaves and indentured servants). The last port of clearance or the immediate destination is also usually given. Sometimes information about where and when bond was given is also included. Thus the lists contain detailed information about the conduct of trade. The data quality and level of detail within these lists does vary between colonies as it was highly dependent on the diligence or otherwise of the administration's Naval Officer.
Date range: 1678-1825.
Keywords: Trade routes -- United States -- History; Trade routes -- Canada -- History; Trade routes -- West Indies -- History; Great Britain -- Commerce -- History